Household air pollution and under-five mortality in sub-Saharan Africa: an analysis of 14 demographic and health surveys - Fanuel Meckson Bickton; Latif Ndeketa; Grace Thandekire Sibande; Juvenal Nkeramahame; Chipiliro Payesa; Edith B. Milanzi (Komiyama Printing Co. Ltd, 2020)
Abstract Background Globally, over four million deaths are attributed to exposure to household air pollution (HAP) annually. Evidence of the association between exposure to HAP and under-five mortality in sub-Saharan Africa (SSA) is insufficient. We assessed the association between exposure to HAP and under-five mortality risk in 14 SSA countries. Methods We pooled Demographic and Health Survey (DHS) data from 14 SSA countries (N = 164376) collected between 2015 and 2018. We defined exposure to HAP as the use of biomass fuel for cooking in the household. Under-five mortality was defined as deaths before age five. Data were analyzed using mixed effects logistic regression models. Results Of the study population, 73% were exposed to HAP and under-five mortality was observed in 5%. HAP exposure was associated with under-five mortality, adjusted odds ratio (OR) 1.33 (95% confidence interval (CI) [1.03-1.71]). Children from households who cooked inside the home had higher risk of under-five mortality compared to households that cooked in separate buildings [0.85 (0.73-0.98)] or outside [0.75 (0.64-0.87)]. Lower risk of under-five mortality was also observed in breastfed children [0.09 (0.05-0.18)] compared to non-breastfed children. Conclusions HAP exposure may be associated with an increased risk of under-five mortality in sub-Saharan Africa. More carefully designed longitudinal studies are required to contribute to these findings. In addition, awareness campaigns on the effects of HAP exposure and interventions to reduce the use of biomass fuels are required in SSA.